The results and the consequences of barbarian conquests of Bosnian-Herzegovinan area - Omerčević, Bego; Imamović, Mersiha (Historical Thought, 2025)
At the end of the 4th century, first ever intrusions of Barbarian peoples in the Bosnian-Herzegovinian area emerged. They were mainly of robbing and vandalising character. As a consequence of the Barbarians’ appearance, there were significant changes in the lives and work of the then population of present-day Bosnia and Herzegovina. Later on, in the period from the 5th century to the beginning of the 7th century, Barbarian vandalism intensified. Its sense was significantly changed. As time passed by, the determination amongst the Barbarian 11 Rezultati i posljedice barbarskih osvajanja bosanskohercegovačkih prostora tribes not to return where they came from kept being stronger. In relation to that, they completely focused on permanent possession, settelement and stay in the areas they had conquered, establishment of government and usage of natural resources and domestic work force, all for the sake of meeting their own daily needs. In such circumstances, the local population was exposed to all kinds of Barbarian torture. Because of that, many inhabitants abandoned their century-long homes and sought sanctuary in other, relatively speaking, safer parts of the Roman Empire.